First-principles investigations of transition-metal doped bilayer WS2. Issue 15 (24th March 2016) - Yang, Yi; Fan, Xiao-Li; Pan, Rui; Guo, Wen-Jun
Abstract : The structural, electronic and magnetic properties of the AA and AB configurations of bilayer WS2 with a TM (Mn, Fe, Co, Ni) doped in the interlayer position were studied by performing first-principles calculations. Abstract : By performing first-principles calculations, we have studied the structural, electronic and magnetic properties of transition-metal (TM) (Mn, Fe, Co, Ni) doped bilayer WS2 in both the AA and AB configurations. We have examined three probable interlayer doping positions, and found that the doped TM atoms prefer to stay below the S atoms. The TM atoms are covalently bound to the upper layer and lower layer S atoms with binding energies ranging from −0.74 to −1.72 eV for the AA configuration and from −0.69 to −1.80 eV for the AB configuration. Our calculations indicate that all the studied configurations are still semiconductors although the corresponding band gaps reduce a lot, except for the Fe-doped AA configuration which changes to a semi-metal with one spin state cross over at the Fermi level. Additional, our calculations indicate that Mn, Fe and Co-doping induces magnetism in both the AA and AB configurations. More importantly, a high spin polarization of 100% at the Fermi level is achieved in the Co-doped AA configuration and the Mn and Fe-doped AB configurations, which implies the potential for application in spintronic devices.